(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: AMD is a common cause of irreversible blindness in the elderly and has a high prevalence and a tendency to progressing. Materials and methods: There were studied disturbance of cellular immunity in 78 patients with the dry form of age-related macular degeneration. Results: The positive effect of the treatment on the cellular level of systemic immunity. After treatment, the concentration of IL-l?, IL-l?, and NTF-? decreased to 18.3 %, 29.6 % and 36.9 % respectively, while IL-4 levels increased by 63.7 %, the concentration of TGF- ? before the treatment was higher by 57.2 %; after treatment, the concentration of TGF-? decreased by 24 %. Conclusion: It was established that the use of immunotropic drugs in patients with AMD helped normalize cellular immunity, which was not observed in the control group as well as to reduce the content and IgA TGF-?, normalization of the normal ratio of pro- and anti-inflammatory cytokines in the lachrymal fluid.